2021
DOI: 10.1164/rccm.202106-1550st
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring Access to Albuterol in Schools: From Policy to Implementation. An Official ATS/AANMA/ALA/NASN Policy Statement

Abstract: Rationale: For children with asthma, access to quick-relief medications is critical to minimizing morbidity and mortality. An innovative and practical approach to ensure access at school is to maintain a supply of stock albuterol that can be used by any student who experiences respiratory distress. To make this possible, state laws allowing for stock albuterol are needed to improve medication access. Objectives: To provide policy recommendations and outline steps for passing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…of National School Nurse Workforce Study participants did (Volerman et al, 2021). Demographic information was not collected, so we cannot speak to the representativeness of our sample in terms of race, ethnicity, sex, or geographic location.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…of National School Nurse Workforce Study participants did (Volerman et al, 2021). Demographic information was not collected, so we cannot speak to the representativeness of our sample in terms of race, ethnicity, sex, or geographic location.…”
Section: Resultsmentioning
confidence: 99%
“…Our cross‐sectional study had some limitations. We had a low response rate (8%) and likely had a response bias‐ nurses serving only one school may have had more time to take the survey and therefore been overrepresented in our dataset, potentially explaining why only 32% of nurses in our survey served two or more schools, but 67.2% of National School Nurse Workforce Study participants did (Volerman et al., 2021). Demographic information was not collected, so we cannot speak to the representativeness of our sample in terms of race, ethnicity, sex, or geographic location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stock albuterol inhaler use in schools is safe and effective, ensuring that all children have access to their rescue medication while at school, with important recent scientific advances [41 ▪▪ ,42 ▪▪ ]. Stock albuterol use has been shown to avoid the need for escalated care such as summoning the emergency medical system and allows children to remain in school when experiencing asthma symptoms [41 ▪▪ ,43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 18 U.S. states have passed legislation that allows schools to procure, stock and administer stock albuterol to students; however, these laws vary widely across states [45 ▪▪ ]. Expert organizations have created policy recommendations that guide states on lobbying for stock inhaler legislation and provides recommendations for program implementation on a state level [42 ▪▪ ]. Recently, stock inhaler events were examined among 228 schools located in Tucson, Arizona, and data suggested that not only were stock inhalers used by all schools across the socio-economic spectrum, but all children can benefit from having a stock inhaler at their school (with no adverse events reported) [46].…”
Section: Introductionmentioning
confidence: 99%